Characterization of Alpha Particle Track Lengths in LR-115 Detectors - Stuani Pereira, Luiz Augusto; Tello Sáenz, Carlos Alberto [UNESP] (MDPI, 2025)
We investigate the dependence of the maximum etched track length (Lmax) on alpha-particle energy and incidence angle in LR-115 type II nuclear track detectors by combining Geant4 Monte Carlo simulations with controlled chemical etching experiments. The bulk (VB) and track (VT) etch rates were determined under standardized conditions, yielding VB=(3.1±0.1) µm/h and VT=(5.98±0.06) µm/h, which correspond to a critical detection angle of about (58.8±1.2)°. Simulations covering initial energies spanning 1 MeV to 5 MeV and incidence angles up to 70° confirmed that the maximum etched track length varies quadratically with particle energy E and depends systematically on incidence angle θ. Empirical parameterizations of Lmax(E,θ) were obtained, and energy thresholds for complete track registration within the 12 µm sensitive layer were established. The angular acceptance predicted by the VT/VB ratio was validated, and the results demonstrate that Lmax provides a monotonic and more reliable observable for energy calibration compared to track diameter. These findings improve the quantitative calibration of LR-115 detectors and strengthen their use in environmental radon monitoring, radiation dosimetry, and alpha spectrometry. In addition, they highlight the utility of Geant4-based modeling for refining solid state nuclear track detector response functions and guiding the development of optimized detector protocols for nuclear and environmental physics applications.